Understanding ChatGPT: A Worldview Study - Bramantyo Suryo Nugroho; Muhammad Azhar Muttaqin; Iftitah Afiat Mulia Insani; Muchammad Taufiq Affandi (TSAQAFAH, 2024)
This study was a critical assesment of epistemological standpoint concerning how the development of western epistemology in ‘text generating’ technology. From the Islamic perspective, the tradition of khabar shadiq, which is based on revelation and ethics, serves as the foundation of knowledge, differing from the Western view that relies more on the scientific method and various data sources, including big data. Modern technology, such as ChatGPT, which utilizes big data, raises ethical and epistemological questions in the Islamization of science. ChatGPT itself faces limitations in its knowledge, while big data often encounters issues of inaccuracy and bias. Therefore, serious consideration is needed regarding ethics in developing and using technology like ChatGPT and its alignment with Islamic values in modern technology. This study highlights the importance of how far the islamic epistemology contrasting western epistemology in developing the technology from the Islamic worldview perspective.